Assessment of timber value and carbon credits provided by pure and mixed forests in Taiwan - Lin, Yow-Ru; Liu, Wan-Yu (Frontiers in Forests and Global Change, 2023)
Introduction: Clear-cutting an even-aged pure forest is a conventional forest operation for wood production. However, this type of operation is unsuitable for sustainable management with multiple disadvantages. By contrast, mixed forests are a forestation strategy that accommodates diversity. This study aims to assess and compare the timber value and carbon credits of a pure forest and a mixed forest, which is transformed from a pure forest. Two alternative options in managing plantations of pure forest (with C. japonica) and mixed forest (with part of C. japonica cut and C. camphora replanted) are evaluated considering both timber value and carbon credits. Scenarios with various harvesting intensities and carbon payments were also considered. Method: A theoretical model was applied, converting pure forest into mixed forest, then two species are cut or replanted in the second round. By contrast, in the pure forest situation, the setting for the second rotation period is a pure forest for 20 years. The model was applied in a simulation experiment and the study area is Taiwan. The selected tree species are representative and have been chosen for analysis. Results: This study showed that even-aged pure forests had higher wood sales and lower carbon payments than uneven-aged mixed forests. The net present value from market value would be from -255,403 NTD ha -1 to -74,134 NTD ha -1 and that from carbon value will be from 156,076 NTD ha -1 to 208,937 NTD ha -1 . Discussion: This study showed strategies by which values could be increased during the transition from an even-aged pure forest to a mixed forest. Feasible methods included reducing the costs of reforestation, management, and cutting while increasing carbon prices to increase profits from wood and carbon income. A higher harvesting intensity could contribute to greater production and increase the area available for planting, resulting in greater profits from wood and carbon income.